Trajectories selected papers in East Asian studies 軌跡 - Sagiyama, Ikuko; CASTORINA, Miriam (Studi e saggi, 2019)
This volume gathers artiche related to different research areas within the field of East Asian Studies. Organized in a Japanese and a Chinese section, these studies use different approaches within humanities disciplines to explore topics ranging from classical and contemporary East Asian literature to the study of second language acquisition across European and Asian languages. The collection offers an intentionally interdisciplinary approach so to provide a broader perspective on the literatures and languages of Japan and China. The authors featured in the volume are Claudia Iazzetta, Luca Capponcelli, Gala Maria Follaco for the Japanese section and Lara Colangelo, Franco Ficetola and Xu Hao for the Chinese section.